Computer-aided design of matched converter-motor pair for induction drives based on effective harmonic utilization - Bhattacharyya N.; Singh G.K. (My University, 2025)
Present trends in the design of asynchronous drive systems is to use standard induction machines in conjunction with solid-state converters with minimized time-harmonics in their supply profile, The paper proposes an alternative approach wherein the seeming ill-effects of time-harmonics may be used with advantage in improving the torque developed in the drive systems. This approach, named the 'Dual Convergence Approach', leads to the design of matched converter motor pair, with specially designed motors capable of using select time-harmonics in supply and is readily amenable to computerizationp both for design and selection of the system. Designs based on proposed methodology have been extensively tested with encouraging results. © 1991 IEEE.